Seroprevalence of hepatitis B virus among patients at a rural tertiary health care centre in South India: a four year study - G., Vazhavandal; B., Vallab Ganesh Bharadwaj; A., Uma; P., Chitra Rajalakshmi (International Journal of Research in Medical Sciences, 2017)
Background: Infection with the Hepatitis B Virus (HBV) is a global health problem. Epidemiological studies worldwide show wide variations in the prevalence patterns of the Hepatitis B infections. Early detection can contribute substantially to the timely diagnosis of the patients with acute illnesses and to an early treatment and hence, it can limit the transmission of the infection. Aim: To provide a baseline data on the prevalence of Hepatitis B among the patients who were attending Chennai Medical College Hospital and Research Centre, Trichy, Tamilnadu, over a period of 4 years (2010-2013). Methods: This was a retrospective study which was carried out among 19,513 patients who were attending the rural tertiary care teaching hospital, Trichy, over a period of 4 years (January 2010 – December 2013). The sera were screened for the presence of Hepatitis B surface antigen (HBsAg) by HEPACARD. Those found positive on screening test were confirmed by Enzyme linked Immuno-sorbent Assay (ELISA) test. Results: Out of 19,513 sera which were studied, 315 (1.61%) were sero-positive cases. Among the positive cases (315), the seroprevalence in males and females were 73% (230) and 27% (85) respectively and the frequency of HBV among age groups 0-20, 21-40, 41-60, >60 was 5.07% (16), 45.07% (142), 35.9% (113),11425% (36) respectively. Among the positive cases, a majority were in the age group of 21 to 40 years, with a male preponderance (p<0.05). Conclusion: The overall prevalence for this HBsAg marker among the patients who attended the rural tertiary teaching hospital in this study was comparatively similar to that which was reported by other studies from India.